Management of in- and out-of-hospital screening for hepatitis C - Jing Zhou; Fa-Da Wang; Lan-Qing Li; En-Qiang Chen (Frontiers Media S.A., 2023)
Because of insidious progression and no significant clinical symptoms at early stage, chronic hepatitis C (CHC) is often diagnosed after the occurrence of cirrhosis and hepatocellular carcinoma. Highly effective and low drug resistance of direct-acting antiviral agents (DAAs) have enabled cure of CHC, encouraging the World Health Organization to propose a global viral hepatitis elimination program. To Date, vaccine for CHC is still under research. Therefore, reducing the source of infection is an important means of eliminating CHC other than cutting off the transmission route, which requires screening, diagnosing and treating as many patients in the population as possible. Hospital-based screening strategy have been found to be cost-effective in the management of CHC screening, as reported both nationally and internationally. Currently, China has issued In-hospital process for viral hepatitis C screening and management in China (Draft) in April, 2021, which provides a standardized implementation process and direction for in-hospital hepatitis C screening and treatment, but still requires medical institution to develop its own management process, taking into account its current situation and learning from domestic and international experience. In addition, screening for CHC outside the hospital among special populations, such as blood donors, pregnant women, homosexuals, intravenous drug users, prisoners, and residents in rural areas with scarce medical care resources, also requires attention and development of targeted and rational screening strategies. In this paper, we analyze and recommend the management of hepatitis C screening from both in-hospital and out-of-hospital perspectives, with the aim of contributing to the formulation of hepatitis C screening strategies.